Gruesome nursery rhymes in Chinese Mother Goose rhymes - Wang, Aiqing (Diksi, 2023)
åºåæŒå›¾ Ruzi Ge Tu "˜Chinese Mother Goose Rhymes' is an anthology cumulated, rendered and illustrated by Isaac Taylor Headland (1859-1942) in 1900, which comprises 152 nursery rhymes predominantly prevailing in Beijing during the Qing (1644-1912) dynasty and aims to nurture sympathy for Chinese children and paint portraits of the masses from both ends of the social spectrum. Chinese nursery rhymes are replete with depictions pertaining to familial bonds and adoration, yet they simultaneously abound with fiendish plots and representations in graphic detail as well as political statements alluding to historical events and personages, parallel to their Western counterparts. In Chinese Mother Goose Rhymes, there is a range of nursery rhymes concerning decease, suicide, impoverishment, dilapidation and animal abuse, whereas only a proportion of them entail educational purposes and convey moral values.